Synthesis and thermal conductivity improvement of W-Cu composites modified with WC interfacial layer. (5th August 2017) - Zhang, Chengcheng; Luo, Guoqiang; Zhang, Jian; Dai, Yang; Shen, Qiang; Zhang, Lianmeng
Abstract: In this study, the WC doped W-Cu composites with high excellent thermal conductivity were fabricated by using coated composite powders combined with vacuum hot-pressure sintering. As-received W powders were pre-modified with organic additives via pyrolysis process (carburization process), and then Cu coated by electroless plating. The WC formed in situ doped W-Cu composite was obtained. X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) techniques were used to characterize the composite powders and sintered composites. The results show that the structure of coated composite powders was W/C/Cu and the structure of sintered sample turned into W/WC/Cu. Both Cu matrix network and WC interfacial layer were obtained in the W-Cu composite. Compared with the W-20 wt%Cu composite without WC modification, the WC doped W-20 wt%Cu composite have excellent thermal conductivity (287.5 W/(m·K)), low coefficient of thermal expansion (4.40 ppm/k) and relatively high Vickers hardness (230.5 HV). The excellent properties are mainly because of Cu network structure formed and its interfacial layer WC yielding improved bonding between the W and Cu matrix. Graphical abstract: Highlights: The WC doped W-Cu composite was obtained via pyrolysis process, electroless Cu plating and hot-press sintering. The WC yielded improved bonding between the W and Cu, with increase in thermal conductivity (239 W/(m·K)).